2001
DOI: 10.1038/86906
|View full text |Cite
|
Sign up to set email alerts
|

Trinucleotide expansion in haploid germ cells by gap repair

Abstract: Huntington disease (HD) is one of eight progressive neurodegenerative disorders in which the underlying mutation is a CAG expansion encoding a polyglutamine tract. The mechanism of trinucleotide expansion is poorly understood. Expansion is mediated by misaligned pairing of repeats and the inappropriate formation of DNA secondary structure as the duplex unpairs. It has never been clear, however, whether duplex unpairing occurs during mitotic replication or during strand-break repair. In simple organisms, trinuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
201
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(215 citation statements)
references
References 28 publications
11
201
3
Order By: Relevance
“…The data showing the lack of measurable effects of meiotic events on the frequency of ESTR mutation in the male germline is consistent with the results of our previous study which failed to detect any correlation between meiotic crossing over and ESTR mutation induction [18]. Using a similar approach for cell sorting and a small-pool PCR technique, the frequency of microsatellite mutation was studied in transgenic mice carrying expanded disease-causing human microsatellite [19]. The results of this study showed that microsatellite expansion almost exclusively occurs in haploid spermatids and thus may be attributed to the repair of DNA gaps within repeats inappropriately folded into secondary structures.…”
supporting
confidence: 90%
“…The data showing the lack of measurable effects of meiotic events on the frequency of ESTR mutation in the male germline is consistent with the results of our previous study which failed to detect any correlation between meiotic crossing over and ESTR mutation induction [18]. Using a similar approach for cell sorting and a small-pool PCR technique, the frequency of microsatellite mutation was studied in transgenic mice carrying expanded disease-causing human microsatellite [19]. The results of this study showed that microsatellite expansion almost exclusively occurs in haploid spermatids and thus may be attributed to the repair of DNA gaps within repeats inappropriately folded into secondary structures.…”
supporting
confidence: 90%
“…MSH2-MSH3 also plays an important role in trinucleotide repeat expansion, the process that underlies several hereditary and progressive neurodegenerative diseases such as Huntington disease, myotonic dystrophy, and fragile-X syndrome (Cummings and Zoghbi, 2000). In the mouse, somatic and germline expansions of the CAG-CTG repeat within the Huntington's gene requires MSH2 (Kovtun and McMurray, 2001;Manley et al, 1999;Wheeler et al, 2003). Repeat instability is reduced in MSH3-null mice but elevated in MSH6-null mice pointing to a role for MSH3 in promoting repeat instability (van den Broek et al, 2002).…”
Section: Other Functions Of Mmrmentioning
confidence: 99%
“…Using a Huntington disease mouse model, carrying a high number of CAG repeats, McMurray and Kovtun demonstrated that the repeat expansion was occurring between round spermatids and spermatozoa [McMurray and Kortun 2003]. Interestingly, the deletion of MSH2 in this mice model abolished the expansion [Kovtun and McMurray 2001], suggesting that MSH2 is active when extensive DNA repair occurs. Additional efforts are needed to identify the proteins involved in the repair process of ES.…”
Section: Further Evidence Of a Dna Repair System In Spermatidsmentioning
confidence: 99%